Hard rock seismic exploration of ore deposits in Australia - Urosevic, Milovan; Kepic, Anton; Juhlin, C.; Stolz, E. (Society of Exploration Geophysics, 2008)
We present an overview of the developments and achievements, over the past four years in the application of seismic reflection methods for mineral exploration in Australia. We show that seismic methods can be successfully used to delineate exceptionally complex hard rock environment in Australia providing that the acquisition parameters and data processing strategy are adequate for the task. Moreover methodologies for the direct targeting of specific ore reserves as well as rock identification from seismic data are discussed.